Telenursing on primary family caregivers and children with disabilities: a scoping review - Nishigaki, Kaori; Yamaji, Noyuri; Adachi, Naho; Kamei, Tomoko; Kobayashi, Kyoko; Kakazu, Shota; Yonekura, Yuki (Frontiers in Pediatrics, 2025)
IntroductionDespite the need for continued support for children with disabilities and their families, COVID-19 has made the support difficult. Telenursing can monitor daily life and support from a remote location, continuously and at a low cost. However, there are few practical reports on its use in children with disabilities.ObjectiveThis scoping review aims to summarize the published literature on telenursing for children with disabilities in home care settings.MethodsWe included studies involving children (0–18 years of age) with disabilities and their families and specified telecommunication assessment, monitoring, and intervention such as tele-education, teleconsultation and telementoring involving nurses via information communication technologies. We included studies that used any design written in English or Japanese. A comprehensive search was conducted on March 14, 2021 using six databases: MEDLINE via PubMed, Cumulative Index to Nursing & Allied Health Literature, Cochrane Central Register of Controlled Trials, Embase, PsycINFO, and Ichushi Web. Two or more reviewers individually screened eligible studies according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses flow diagram. Data on the characteristics of the included studies, telecommunications technology interventions, and children with disabilities were mapped in tables.ResultsEleven studies, published between 2003 and 2020, met the inclusion criteria. Only one study used the term “telenursing,” while others used “telehealth” and other terms, which involved multidisciplinary support such as physicians and social workers in addition to nurses. Although there were various types of telecommunications technology interventions, they were categorized as consultation, healthcare provision, monitoring, and education. Most studies have examined telecommunication technology interventions by healthcare professionals, including nurses. Five studies focused on children with medical complexities, and two focused on children with neurodevelopmental disabilities, including developmental delays. There is insufficient information on telecommunications technology interventions, especially assessment tools, trigger points, and the status of the target population.ConclusionThis scoping review aimed to map the published literature on telenursing for children with disabilities and their families in home care settings. Available evidence indicates a lack of research focusing on the implementation of telecommunications for children with disabilities and their families. Further research is required to assess the effects of telecommunications technology interventions. Additionally, they should provide information for implementing telecommunication technology safety.Scoping Review RegistrationFigshare (https://doi.org/10.6084/m9.figshare.21747047.v1).